Emerging Trends in SSD Technology for AI Applications: A Comprehensive Analysis - Gupta, Sameeksha (International Journal of Computing and Engineering, 2025)
The merging of solid-state storage technology with artificial intelligence has sparked unmatched innovation in storage design, fundamentally altering how AI systems retrieve and manage data. This article explores the developing realm of SSD technologies tailored for AI workloads, advancing past conventional performance metrics to tackle the distinct challenges faced during model training and inference. From the constraints of traditional NAND-based approaches to the ground-breaking capabilities of computational storage and modern non-volatile memory technologies, the article examines how these advancements redefine the limits between storage and computation. The article shows that technologies like 3D XPoint, phase-change memory, and computational storage drives provide significant advantages for AI applications—shortening training times, decreasing inference latency, and facilitating more efficient implementation of large language models. However, considerable implementation obstacles remain, such as framework compatibility, cost-benefit factors, and complexities in enterprise integration. Anticipating future developments, the article emphasizes encouraging avenues in quantum storage, neuromorphic integration, and standardization initiatives that will boost the collaborative advancement of storage and AI. For entities developing AI infrastructure, these advancements signify not just gradual enhancements but a transformative change that treats storage as an engaged contributor in AI computation instead of a mere passive data repository.